2013
DOI: 10.1111/1758-2229.12072
|View full text |Cite
|
Sign up to set email alerts
|

Confined aquifers as viral reservoirs

Abstract: SummaryKnowledge about viral diversity and abundance in deep groundwater reserves is limited. We found that the viral community inhabiting a deep confined aquifer in South Australia was more similar to reclaimed water communities than to the viral communities in the overlying unconfined aquifer community. This similarity was driven by high relative occurrence of the single-stranded DNA viral groups Circoviridae, Geminiviridae and Microviridae, which include many known plant and animal pathogens. These groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
3
19
1
Order By: Relevance
“…Considering that only four complete ssDNA viral genomes were identified in Ichetucknee Springs, our study supports the idea that in some aquatic environments, a few ssDNA viruses can be among the most abundant viruses contributing to the community composition (47). These findings are also consistent with a previous study that demonstrated elevated levels of ssDNA viruses in aquifer systems (22). However, the 2013 study by Smith et al used multiple-displacement amplification, which has a known bias toward small circular genomes such as those of ssDNA viruses, making it difficult to derive quantitative information from their sequence data (22,50).…”
Section: Figsupporting
confidence: 91%
See 4 more Smart Citations
“…Considering that only four complete ssDNA viral genomes were identified in Ichetucknee Springs, our study supports the idea that in some aquatic environments, a few ssDNA viruses can be among the most abundant viruses contributing to the community composition (47). These findings are also consistent with a previous study that demonstrated elevated levels of ssDNA viruses in aquifer systems (22). However, the 2013 study by Smith et al used multiple-displacement amplification, which has a known bias toward small circular genomes such as those of ssDNA viruses, making it difficult to derive quantitative information from their sequence data (22,50).…”
Section: Figsupporting
confidence: 91%
“…These findings are also consistent with a previous study that demonstrated elevated levels of ssDNA viruses in aquifer systems (22). However, the 2013 study by Smith et al used multiple-displacement amplification, which has a known bias toward small circular genomes such as those of ssDNA viruses, making it difficult to derive quantitative information from their sequence data (22,50). Ichetucknee Springs is one of few environments reported where certain ssDNA viruses are more abundant than dsDNA viruses (47).…”
Section: Figsupporting
confidence: 87%
See 3 more Smart Citations